Študij zamreževanja nasičenega poliestra s heksametoksimetilmelaminom z infrardečo spektroskopijo - Leskovšek, Nevenka (Kovine zlitine tehnologije, 1995)
Ecological problems, due to the evaporation of organic solvents, are the main reason for application high solid coatings in which binders with lower molecular weight are used. Crosslinking of low molecular weight polymers requires special attentions since greater number of bond must be formed to crosslink the resin binder as in the classical paint systems. The influence of the temperature and catalyst on crosslinking reactions was followed by FTIR spectriscopy in -OH terminated polyester/hexamethoxymethyl melamine clearcoat.The main reaction of transetherification between hydroxy groups on polyester and methoxy groups on melamine was accompanied by several side competative reactions.
Keywords: premazi; poliester; zamreževanje